WAKTU OPTIMUM PRODUKSI DAN KONSUMSI OKSIGEN RUMPUT LAUT GRACILARIA VERRUCOSA - Kartono, Kartono; Izzati, Munifatul Izzati (MATEMATIKA, 2010)
Seaweed Gracilaria verrucosa not only produce oxygen but also consume oxygen. Consider the production and consumption of the oxygen, we can determined that the production and consumption models of oxygen like a logistic models. Finally, in this paper presented a role to determine an optimum time of the oxygen production and consumption.